Transformasi Literasi Keuangan melalui Pendekatan Gamifikasi dengan Game Jack Milyarder - Naca Perangin-Angin; Pioner Pelawi; Fanny Fanny; Tya Wildana Hapsari Lubis; Hanny Siagian (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The gamification approach plays a crucial role in providing understanding, insights, and skills for financial management needs. Amid economic challenges, a solid understanding of financial management assists in decision-making. One innovation in introducing digital literacy transformation in a fun and more engaging way is through the Jack Milyarder game. This aims to introduce and enhance financial literacy understanding at SMA Tri Ratna Sibolga. The results of this community service project show that gamification through Jack Milyarder successfully provided an understanding of digital literacy transformation for students at SMA Tri Ratna Sibolga. The implemented learning method successfully bridged the gap in students' initial knowledge and provided a better understanding of important topics in financial literacy.